2017
DOI: 10.1002/elsc.201700084
|View full text |Cite
|
Sign up to set email alerts
|

In‐line monitoring of amino acids in mammalian cell cultures using raman spectroscopy and multivariate chemometrics models

Abstract: In-line monitoring of amino acids in mammalian cell cultures using raman spectroscopy and multivariate chemometrics modelsThe application of PAT for in-line monitoring of biopharmaceutical manufacturing operations has a central role in developing more robust and consistent processes. Various spectroscopic techniques have been applied for collecting real-time data from cell culture processes. Among these, Raman spectroscopy has been shown to have advantages over other spectroscopic techniques, especially in aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 28 publications
1
37
0
Order By: Relevance
“…Several inline spectroscopic methods including Near Infrared (NIR), 2D‐Fluorescence, and Raman have been proposed for continuous cell culture monitoring . NIR measures the region between 800 and 2500 nm and collects information about the overtones of fundamental absorption bands observed in more traditional mid‐IR applications .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several inline spectroscopic methods including Near Infrared (NIR), 2D‐Fluorescence, and Raman have been proposed for continuous cell culture monitoring . NIR measures the region between 800 and 2500 nm and collects information about the overtones of fundamental absorption bands observed in more traditional mid‐IR applications .…”
Section: Introductionmentioning
confidence: 99%
“…However, the Raman signal is generally lower compared to elastically scattered light (≈1,000 times less) and is sensitive to interference from fluorescent molecules which can lead to baseline offsets . Even with these limitations Raman spectroscopy, has seen increased use in applications for monitoring bioreactor process parameters in recent years . Furthermore, a recent evaluation by Rowland‐Jones et al comparing NIR, 2D‐fluorescence, and Raman identified Raman as more suitable for analysis of the contents of a miniature bioreactor …”
Section: Introductionmentioning
confidence: 99%
“…In spectroscopy‐based bioprocess monitoring, it has been shown that numerous variables such as metabolites, cell density, and titer can be predicted based on the spectra . Recent examples illustrate the application of PLSR‐based calibration models to monitor several amino acids in cell culture processes …”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] Recent examples illustrate the application of PLSR-based calibration models to monitor several amino acids in cell culture processes. 27,28 However, linearity is one of the major limitations of the PLSR approach for bioprocessing analysis due to the high level of nonlinear dynamic effects. 18 Several studies attempted to overcome these by utilizing nonlinear data analysis approaches such as artificial neural networks (ANN).…”
Section: Introductionmentioning
confidence: 99%
“…As a noninvasive and nondestructive process analytical technology (PAT) tool, Raman spectroscopy has attracted attention because it produces detailed molecular fingerprints with high chemical specificity, does not require sample preparation and is suitable for aqueous system analysis with only weak signals from water when compared with NIR spectroscopy. In a recent study conducted by Bhatia et al ., the significant potential of Raman spectroscopy for quantification of Tyr, Trp and Phe was demonstrated. Additionally, quantification and monitoring of Glu and other analytes by Raman spectroscopy in cell cultures have been reported in several studies .…”
Section: Introductionmentioning
confidence: 99%